PEMANFAATAN KOTORAN TERNAK SAPI SEBAGAI SUMBER ENERGI ALTERNATIF RAMAH LINGKUNGAN BESERTA ASPEK SOSIO KULTURALNYA - Rahayu, dkk, Sugi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
AbstractThe objectives of this activity are: (1) improving knowledge aboututilization of biogas from livestock dirt for farmer society and ranchers; (2)giving information about aspect of sosiocultural in utilization of biogas inorder to build new businessman; (3) evaluating utilization of prospect ofbiogas at Jatisarono, Nanggulan, Kulonprogo related to aspect of communitydevelopment for range longer.The target of this activity is cows ranchers at Jatisarono, Nanggulan,Kulon progo. As for execution methods weared in this activity are experiment,discourse, discussion of information and presentation. The materialsare cow livestock dirt for alternative friendly environment fuel, cow livestockdirt energy conversion and aspect sosio cultural of biogas.This activity has been succeeded in understanding and detectingresidue utilization of biogas from livestock dirt for farmer society and cowranchers at Jatisarono. Through this activity, aspect of sosio-cultural oftechnology biogas in order to build new businessman has been understoodby farmer society and cow ranchers at Jatisarono and detect prospecteverything that can be developed related to utilization of technology biogasat Jatisarono in order to community development for range longer.Keywords: biogas, sosio cultural, and fuel